A Proposed Approach for Enhancing Human Resource Quality at PT Mandiri Sawit Bersama - Hasibuan, Zerimah Afgani; Sugianto; Syarbaini, Ahmad Muhaisin B. (Jurnal Manajemen Bisnis, 2023)
Enhancing the calibre of personnel within a firm holds significant importance as it not only impacts the overall level of work productivity, but also holds the potential to elevate the quality of performance within the organisation. The objective of quality improvement is to enhance the technical, theoretical, conceptual, and moral competencies of employees, so ensuring their ability to deliver exceptional information to both existing and potential clients. In order to effectively promote these products, it is imperative for staff to possess a comprehensive understanding of the consumer market's desires. The provision of high-quality service is intricately linked to the enhancement of human resources. The objective of this study is to provide a comprehensive description of the technique employed to enhance the quality of work among employees at PT. Mandiri Sawit Bersama. The quantity of samples obtained through the utilisation of the purposive sampling technique. This study employs qualitative descriptive approaches, employing qualitative descriptive analytic tools for data analysis. Based on the findings derived from the conducted research, it was determined that out of the three strategies aimed at enhancing the calibre of human resources inside the organisation, two of them exhibit a comparatively lesser impact on the overall quality of human resources in the company. This observation indicates that the strategy is not implemented in a direct manner, but rather its impact is confined to influencing the performance of employees in executing assigned duties.